2021
DOI: 10.1111/exd.14459
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive evaluation of subjective sensitive skin by transcriptomics using mRNA in skin surface lipids

Abstract: Sensitive skin is a condition characterized by hypersensitivity to environmental stimuli, and its pathophysiology has not been fully elucidated. Questionnaires based on subjective symptoms, intervention tests, and measuring devices are used to diagnose sensitive skin; however, objective evaluation methods, including biomarkers, remain to be established. This study aimed to investigate the molecular profiles of self-reported sensitive skin, understand its pathophysiology and explore its biomarkers. Here, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The skin surface lipid RNA profiles also indicated a mild inflammatory state in the sensitive skin group and, overall, olfactory receptor gene expression may be a potential indicator of sensitive skin. 22 Combined with the current production status of lipid standards, GlcCer(d18:1/16:0) and Cer(d18:0/16:0) were finally selected after screening and these two lipid markers were used as samples for subsequent experiments. A comparison of the repair/protective effects of GlcCer and Cer on barrier-damaged HaCaT cells revealed that both had a restorative effect on barrier-damaged HaCaT cells yet did not confer protection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The skin surface lipid RNA profiles also indicated a mild inflammatory state in the sensitive skin group and, overall, olfactory receptor gene expression may be a potential indicator of sensitive skin. 22 Combined with the current production status of lipid standards, GlcCer(d18:1/16:0) and Cer(d18:0/16:0) were finally selected after screening and these two lipid markers were used as samples for subsequent experiments. A comparison of the repair/protective effects of GlcCer and Cer on barrier-damaged HaCaT cells revealed that both had a restorative effect on barrier-damaged HaCaT cells yet did not confer protection.…”
Section: Discussionmentioning
confidence: 99%
“…Uehara et al 22 analyzed the RNA in skin surface lipids, obtained noninvasively by wiping the skin surface with an oil‐absorbing film, to compare participants with questionnaire‐based “sensitive” ( n = 11) and “nonsensitive” ( n = 10) skin. The skin surface lipid RNA profiles also indicated a mild inflammatory state in the sensitive skin group and, overall, olfactory receptor gene expression may be a potential indicator of sensitive skin 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected SSLs from the face and performed purification of SSL-RNAs according to previous reports with a few modifications. 12,13,19,20 Detailed methodology is shown in Appendix S1 for Methodology.…”
Section: Collection Of Ssls Rna Preparation and Ampliseq Transcriptom...mentioning
confidence: 99%